Adherence to Antiretroviral Therapy (ART) in Yaoundé-Cameroon: Association with Opportunistic Infections, Depression, ART Regimen and Side Effects. - Julius Y Fonsah; Alfred K Njamnshi; Charles Kouanfack; Fang Qiu; Dora M Njamnshi; Claude T Tagny; Emilienne Nchindap; Léopoldine Kenmogne; Dora Mbanya; Robert Heaton; Georgette D Kanmogne (PLoS ONE)
Following global efforts to increase antiretroviral therapy (ART) access in Sub-Saharan Africa, ART coverage among HIV-infected Cameroonians increased from 0% in 2003 to 22% in 2014. However, the success of current HIV treatment programs depends not only on access to ART, but also on retention in care and good treatment adherence. This is necessary to achieve viral suppression, prevent virologic failure, and reduce viral transmission and HIV/AIDS-related deaths. Previous studies in Cameroon showed poor adherence, treatment interruption, and loss to follow-up among HIV+ subjects on ART, but the factors that influence ART adherence are not well known. In the current cross-sectional study, patient/self-reported questionnaires and pharmacy medication refill data were used to quantify ART adherence and determine the factors associated with increased risk of non-adherence among HIV-infected Cameroonians. We demonstrated that drug side-effects, low CD4 cell counts and higher viral loads are associated with increased risk of non-adherence, and compared to females, males were more likely to forego ART because of side effects (p<0.05). Univariate logistic regression analysis demonstrated that subjects with opportunistic infections (on antibiotics) had 2.42-times higher odds of having been non-adherent (p<0.001). Multivariable analysis controlling for ART regimen, age, gender, and education showed that subjects with opportunistic infections had 3.1-times higher odds of having been non-adherent (p<0.0003), with significantly longer periods of non-adherence, compared to subjects without opportunistic infections (p = 0.02). We further showed that compared to younger subjects (≤40 years), older subjects (>40 years) were less likely to be non-adherent (p<0.01) and had shorter non-adherent periods (p<0.0001). The presence of depression symptoms correlated with non-adherence to ART during antibiotic treatment (r = 0.53, p = 0.04), and was associated with lower CD4 cell counts (p = 0.04) and longer non-adherent periods (p = 0.04). Change in ART regimen was significantly associated with increased likelihood of non-adherence and increased duration of the non-adherence period. Addressing these underlying risk factors could improve ART adherence, retention in care and treatment outcomes for HIV/AIDS patients in Cameroon.